EFFECT OF CLIMATE CHANGE ON AGRICULTURAL PRODUCTIVITY IN MAGOLA SUB COUNTY IN TORORO DISTRICT - OBWIN ALBERT A_BSWASA_2024.pdf (My University, 2024)
This study assessed the impact of climate change on agricultural productivity in Magola Subcounty, Tororo District, using a cross-sectional survey design with a sample size of 36 respondents. The research aimed to evaluate the effects of greenhouse gas emissions, temperature changes, and sea level rise on agricultural productivity. Findings indicated that greenhouse gas emissions led to a decline in crop yields, altered growth patterns, degraded soil quality, and increased crop diseases. Regression analysis revealed a significant negative correlation between greenhouse gas emissions and agricultural productivity (R = 0.556, R² = 0.309). Temperature changes were found to adversely affect crop yields, complicate planting and harvesting schedules, and induce water stress. Regression results showed a modest yet significant impact of temperature changes on agricultural productivity (R = 0.174, R² = 0.030). Sea level rise exacerbated water scarcity, increased soil salinity, and caused waterlogging. The regression analysis demonstrated a significant correlation between sea level rise and agricultural productivity (R = 0.248, R² = 0.062). The study concluded that climate change presents substantial threats to agricultural productivity in Magola Subcounty. Recommendations included adopting adaptive measures such as improved irrigation systems, heat-resistant crop varieties, and enhanced water management practices. The findings underscored the urgent need for targeted interventions to mitigate the adverse effects of climate change and ensure the sustainability of agricultural productivity in the region.